Big Mean Mike - Knudsen, Michelle (Candlewick Press, 2012)
Mike is proud to be the biggest, toughest dog in the neighborhood, so when tiny, fuzzy bunnies start showing up in his big, mean car he sees them only as a threat to his reputation, no matter how adorable they are.